Strengthening of Profil Pelajar Pancasila in the Dimension of Gotong Royong in the Digital Era through Project Based Learning at MAN 2 Lamongan - Vitiya Avina Aninas; Khotimah Suryani (AJER: Advanced Journal of Education and Religion, 2024)
The Pancasila Student Profile Project is a combination of personality and abilities that must be possessed by students based on the noble values ​​of Pancasila, which was created by the Ministry of Education and Culture in the independent curriculum. The purpose of this study is to describe the implementation of the Project Based Learning to Strengthen the Pancasila Student Profile at MAN 2 Lamongan and to find out the values ​​of mutual cooperation embedded in MAN 2 Lamongan students. The data collection method uses qualitative research with a descriptive approach. Data collection techniques in this study are observation, interviews, documentation. Then the data analysis techniques used are method triangulation, data source triangulation, and theory triangulation. The results of this study on the implementation of PJBL applied in the Pancasila Student Profile activity focus on character education for students in this digital era. In mutual cooperation activities, it is hoped that students will always help each other, be able to work together well, and become individuals with noble character.